Comparison of Outcome between Early Enteral and Total Parenteral Nutrition in Patients with Acute Pancreatitis - FAROOQ, OMER; KHAN, AAMER ZAMAN; HUSSAIN, IMTIAZ (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare the outcome between early enteral and total parenteral nutrition in patients with acute pancreatitis. Methods: This six months randomized controlled trial was carried out at Department of General Surgery, Unit-I, Sir Ganga Ram Hospital, Lahore study. A total of 234 patients of both genders, aged between 18-70 years presenting with acute pancreatitis were included in this study after taking written informed consent. These patients were randomly allocated into two treatment groups. Patients in Group A received early enteral nutrition while Group B received total parenteral nutrition. Need for surgical intervention, length of hospital stay and death was recorded. Patients presented with complications of acute pancreatitis like shock, pancreatic necrosis and pancreatic abscess and diabetic patients were not included in this study. Results: The age of the patients ranged from 18 years to 70 years with a mean of 43.8 years. Majority (49.6%) of the patients belong to age group of 35-50 years. There were 152 (65.0%) male and 82 (35.0%) female. Among them, 39 (59.4%) patients had mild pancreatitis while 39 (16.7%) had moderate and 56 (23.9%) had severe pancreatitis. Both the study groups were comparable in terms of mean age (p=0.764), gender (p=0.584) and severity of pancreatitis (p=0.786). The mean length of hospital stay was significantly shorter with early enteral nutrition (14.7 vs. 17.7 days; p=0.000) as compared to total parenteral nutrition. This difference was significant across all age, gender and disease severity groups. The frequency of surgical intervention (28.2% vs. 82.9%; p=0.000) and death (15.4% vs. 45.3%; p=0.000) was significantly lower in early enteral nutrition group as compared to total parenteral nutrition group irrespective of patient’s age, gender and severity of pancreatitis. Conclusion: The mean length of hospital stay the frequency of surgical intervention and death were all significantly lower in early enteral nutrition group as compared to total parenteral nutrition group irrespective of patient’s age, gender and severity of pancreatitis.